Internalization of Organizational Culture at Sultan Aji Muhammad Idris State Islamic University Samarinda - Muadin, Akhmad; Muslim, Rendy; Salabi, Agus Salim (Idarah (Jurnal Pendidikan dan Kependidikan), 2022)
The purpose of this study is to describe the internalization of organizational culture at UINSI Samarinda. This study uses qualitative research with data collection techniques through observation, interviews and documentation. The data analysis technique is using an interactive data analysis approach data condensation, data presentation and conclusion drawing. The validity of the data was tested using source triangulation and technical triangulation. Sources of data from this study were respondents at the UINSI Samarinda. The results of this study indicate that the internalization of organizational culture at the UINSI Samarinda shows the existence of standard operating procedures, exemplary and motivational as well as advice in the process of implementation. Internalization of organizational culture at Sultan Aji Muhammad Idris Samarinda State Islamic University can be implemented properly by using standard operating procedures as a reference in work, exemplary shown by the leadership as well as motivation and advice from leaders.